Buying and Selling System at the Honesty Canteen in Banjarmasin City from the Syafi'i Madzhab Perspective - Badruddin Ibad (Sharia Oikonomia Law Journal, 2024)
Some schools in Banjarmasin, like SMP 7, use the honest canteen as a government and school strategy to promote honesty among all pupils. Without ever having to interact with the vendor in person, customers of a "honesty canteen" can select the food and drink items they desire and leave payment in an envelope labeled with the total price. Qualitative field research is employed for this study. As long as there is no gharar in the sale and purchase, the findings suggest that the buying and selling system in the honesty canteen is permitted from the perspective of Syafi'i school. The contracting party, the ijab qabul, and the subject matter of the contract are the three pillars of commerce according to the Syafi'i School. The conditions for both buyers and sellers have been met by the contract holders in the honesty canteen. Meanwhile, according to the Syafi'i school, the ijab qabul issue must be resolved before any sale or purchase can be considered legal in the honesty canteen. The Syafi'i school accepts 'urf or tradition, such as what occurred in the honesty canteen of ijab qabul using rehearsing, namely the existence of a price list for each item and the purpose of buyers and sellers to make buying and selling, so honesty canteens that do not use ijab qabul directly are still valid. The items at issue in the agreement are not prohibited from being bought and sold, so the transaction can move forward.